Investigating Pb2 CAP-binding domain inhibitors from marine bacteria for targeting the influenza A H5N1 - Taha A. Kumosani; Aymn T. Abbas; Balogun Basheer; Ahmed M. Hassan; Soonham S. Yaghmoor; Areej H. Alyahiby; Amer H. Asseri; Vivek Dhar Dwivedi; Esam I. Azhar (PLoS ONE, 2025)
The ongoing increase in the prevalence and mutation rate of the influenza virus remains a critical global health issue. A promising strategy for antiviral drug development involves targeting the RNA-dependent RNA polymerase, specifically the PB2-cap binding domain of Influenza A H5N1. This study employs an in-silico approach to inhibit this domain, crucial for viral replication, using potential inhibitors derived from marine bacterial compounds. Utilizing the MTi-OpenScreen web server, we screened a library of compounds to assess their molecular interactions with the target. This process identified four potential inhibitors: CMNPD25830, CMNPD18675, CMNPD18676, and CMNPD27216. Subsequent molecular dynamics simulations, conducted using the Amber software suite, evaluated their binding affinities and dynamic interactions with the PB2 protein. Notably, CMNPD25830 and CMNPD27216 emerged as the most promising candidates, exhibiting higher binding affinities and more favourable interaction profiles compared to the control molecule. Additional analyses, including post-simulation free energy calculations and free energy landscape analysis, strengthened the potential of these compounds as effective PB2-cap binding domain inhibitors. This comprehensive computational investigation identifies CMNPD27216 and CMNPD25830 as standout candidates due to their superior binding energies and dynamic stability, suggesting their strong potential as therapeutic agents against influenza. This research sets the stage for further in vitro validation and optimization of these lead compounds, potentially supporting the development of more effective influenza treatments.